Philanthropic Collaboration: A Conceptual Framework for Giving Circles. (1st November 2020) - Miller-Stevens, Katrina; Taylor, Jennifer A.
Abstract : As the country faces challenges in response to the current political climate, societal tragedies, and environmental disasters, citizens are besieged by nonprofit organizations requesting donations. In response to these requests, individual citizens are seeking out innovative ways to engage in philanthropy. One recent innovation in grassroots philanthropy is giving circles where individuals pool their money, knowledge, and resources to make a social impact. The functions of giving circles can be likened to collaborations in that giving circles encompass the key characteristics of collaboration including communication, consensus decision-making, focusing on common goals, a shared vision and ethical approach, pooling of resources, depending on social capital, and trust. The proposed framework of philanthropic collaboration creates an intersection between the collaboration, philanthropy, and social movement literatures by proving an innovative lens through which to view giving circles. The conceptual framework provides a tool for scholars and practitioners to define and operationalize this new innovation in grassroots philanthropy.